Genome-wide association study and polygenic score assessment of insulin resistance - Aliyu, Usama; Umlai, Umm-Kulthum Ismail; Toor, Salman M.; Elashi, Asma A.; Al-Sarraj, Yasser A.; Abou−Samra, Abdul Badi; Suhre, Karsten; Albagha, Omar M. E. (Frontiers in Endocrinology, 2024)
Insulin resistance (IR) and beta cell dysfunction are the major drivers of type 2 diabetes (T2D).Genome-Wide Association Studies (GWAS) on IR have been predominantly conducted in European populations, whilst and Middle Eastern populations remain largely underrepresented. We conducted a GWAS on the indices of IR (HOMA2-IR) and beta cell function (HOMA2-%B) in 6,217 non-diabetic individuals from the Qatar Biobank (QBB; Discovery cohort; n=2170, Replication cohort; n= 4047) with and without body mass index (BMI) adjustment. We also developed polygenic scores (PGS) for HOMA2-IR and compared their performance with a previously derived PGS for HOMA-IR (PGS003470). We replicated 11 loci that have been previously associated with HOMA-IR and 24 loci that have been associated with HOMA-%B, at nominal statistical significance. We also identified a novel locus associated with beta cell function near VEGFC gene, tagged by rs61552983 (P = 4.38 × 10 -8 ). Moreover, our top best performing PGS (Q-PGS46; Adj R 2 = 0.233 ± 0.014; P = 1.55 x 10 -3 ) performed better than PGS003470 (Adj R 2 = 0.194 ± 0.014; P = 5.45 x 10 -2 ) in predicting HOMA2-IR in our dataset. This is the first GWAS on HOMA2 and the first GWAS conducted in the Middle East focusing on IR and beta cell function. Herein, we report a novel locus in VEGFC that is implicated in beta cell dysfunction. Inclusion of under-represented populations in GWAS has potentials to provide important insights into the genetic architecture of IR and beta cell function.